2007
DOI: 10.1080/03601230701544967
|View full text |Cite
|
Sign up to set email alerts
|

HPLC determination of chlorate metabolism in bovine ruminal fluid

Abstract: Salmonella and Escherichia coli are two bacteria that are important causes of human and animal disease worldwide. Chlorate is converted in the cell to chlorite, which is lethal to these bacteria. An HPLC procedure was developed for the rapid analysis of chlorate (ClO(3)(-)), nitrate (NO(3)(-)), and nitrite (NO(2)(-)) ions in bovine ruminal fluid samples. Standard curves for chlorite, nitrite, nitrate, and chlorate were well defined linear curves with R(2) values of 0.99846, 0.99106, 0.99854, and 0.99138, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Four millilitres rumen fluid and duodenal fluid were filtered with four layers of gauze and centrifuged (3824 g , 10 min). One millilitre ethyl acetate was added to 2 ml supernatant and plasma with sufficient mixing and centrifuged (3824 g , 5 min) to obtain the organic phase (Lodge‐Ivey et al., ; Beier et al., ). The organic phase was dried with nitrogen and dissolved to the mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…Four millilitres rumen fluid and duodenal fluid were filtered with four layers of gauze and centrifuged (3824 g , 10 min). One millilitre ethyl acetate was added to 2 ml supernatant and plasma with sufficient mixing and centrifuged (3824 g , 5 min) to obtain the organic phase (Lodge‐Ivey et al., ; Beier et al., ). The organic phase was dried with nitrogen and dissolved to the mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…Ion chromatography with conductivity detection has been successfully used to measure parts per billion (ppb) concentrations of chlorate in drinking water 25 and, more recently, it has been used to measure the disappearance of chlorate salts from ruminal fluid cultures. 26 In the latter study, accurate measurements of chlorate were limited when chlorate concentrations were <25 ppm. For example, recoveries of analyte at 0.5 and 5 ppm were 718 and 145%, respectively.…”
Section: ' Introductionmentioning
confidence: 94%
“…For lamb urine, chlorate was eluted from these columns using sodium hydroxide mobile phases without interference (data not shown), but when urine from mature animals was analyzed, interferences prevented quantification of chlorate. Beier et al 26 utilized a Dionex AS9 column to quantify chlorate in diluted (1/10) and filtered, but otherwise unprocessed, ruminal fluid samples. Beier et al 26 reported recoveries of 718 and 142% at sample concentrations of 0.5 and 5 ppm, respectively.…”
Section: Lc-ms Analysis Of Chlorate In Animalmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern analytical developments have given rise to liquid chromatography with coupled mass spectral detection (LC‐MS) (Barron & Paull, ; Charles & Pepin, ), but although these methods have been developed for detection in water, their application to complex biological matrices has been explored to a lesser degree (Beier et al., ). Liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) has been developed as a multi‐residue analytical method for polar pesticides (Anastassiades et al., ; Hepperle et al., ) and has been employed by EFSA for the testing of fruits and vegetables for pesticide residues at levels of μg/kg (EFSA, ).…”
Section: Analysis Of Chlorate and Perchloratementioning
confidence: 99%